2017
DOI: 10.18632/oncotarget.15458
|View full text |Cite
|
Sign up to set email alerts
|

Promoter mutations and cellular distribution of telomerase in non-clear cell and clear cell hepatocellular carcinoma

Abstract: Reactivation of telomerase is a critical step in the development of hepatocellular carcinoma (HCC). Here we identified the frequency of mutations in telomerase reverse transcriptase (TERT) promoter was 34% in non-clear cell HCC (NCCHCC, n = 259) and 26.3% in clear cell HCC (CCHCC, n = 57). The mutations were independently associated with poor recurrence-free survival of HCCs. Interestingly immunohistochemical analysis demonstrated a higher positive rate of TERT cytoplasmic localization (95%) than nuclear local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 34 publications
3
18
2
Order By: Relevance
“… a includes cerebellar glioblastoma ( n = 14) [ 50 ], gliomatosis ( n = 10) [ 50 ], glioblastoma with oligodendroglial differentiation ( n = 6) [ 50 ]; b includes oligoastrocytoma (grades II-III) ( n = 58) [ 61 ]; c includes spinal ependymoma ( n = 9); d these cases were not analysed for the TP53 status. There is a partial overlap of the study populations of Eckel-Passow et al [ 71 ] and Pekmezci et al [ 63 ]; e includes grade I-IV hepatocellular carcinoma and clear cell ( n = 57) [ 107 ] and non-clear cell hepatocellular carcinoma, NOS ( n = 259) [ 107 ]; f includes widely invasive ( n = 126) [ 140 ] and minimaly invasive ( n = 44) [ 140 ] Hürthle cell carcinomas; g these cases were classified according to the AFIP criteria [ 220 ]. It does not seem to exist an overlap of the study populations of Landa et al [ 127 ] and Landa et al [ 133 ]; it may exist an overlap of the study populations of Kim et al [ 136 ] and Kim et al [ 137 ] and the study populations of Melo et al [ 125 ] and Melo et al [ 138 ]; h includes buccal ( n = 84) [ 158 ], gum ( n = 34) [ 158 ], lip ( n = 6) [ 158 ], tongue ( n = 63) [ 158 ], floor of mouth ( n = 22) [ 49 , 158 ], alveolar ridge ( n = 1) [ 49 ], mandibule ( n = 1) [ 49 ], hard palate ( n = 2) [ 49 ], supraglottis ( n = 4) [ 49 ], glottis ( n = 1) [ 49 ], tonsil ( n = 18) [ 49 ], larynx ( n = 2) [ 49 ], oropharynx/hypopharynx ( n = 1) [ 49 ] and hypopharynx...…”
Section: Figurementioning
confidence: 99%
“… a includes cerebellar glioblastoma ( n = 14) [ 50 ], gliomatosis ( n = 10) [ 50 ], glioblastoma with oligodendroglial differentiation ( n = 6) [ 50 ]; b includes oligoastrocytoma (grades II-III) ( n = 58) [ 61 ]; c includes spinal ependymoma ( n = 9); d these cases were not analysed for the TP53 status. There is a partial overlap of the study populations of Eckel-Passow et al [ 71 ] and Pekmezci et al [ 63 ]; e includes grade I-IV hepatocellular carcinoma and clear cell ( n = 57) [ 107 ] and non-clear cell hepatocellular carcinoma, NOS ( n = 259) [ 107 ]; f includes widely invasive ( n = 126) [ 140 ] and minimaly invasive ( n = 44) [ 140 ] Hürthle cell carcinomas; g these cases were classified according to the AFIP criteria [ 220 ]. It does not seem to exist an overlap of the study populations of Landa et al [ 127 ] and Landa et al [ 133 ]; it may exist an overlap of the study populations of Kim et al [ 136 ] and Kim et al [ 137 ] and the study populations of Melo et al [ 125 ] and Melo et al [ 138 ]; h includes buccal ( n = 84) [ 158 ], gum ( n = 34) [ 158 ], lip ( n = 6) [ 158 ], tongue ( n = 63) [ 158 ], floor of mouth ( n = 22) [ 49 , 158 ], alveolar ridge ( n = 1) [ 49 ], mandibule ( n = 1) [ 49 ], hard palate ( n = 2) [ 49 ], supraglottis ( n = 4) [ 49 ], glottis ( n = 1) [ 49 ], tonsil ( n = 18) [ 49 ], larynx ( n = 2) [ 49 ], oropharynx/hypopharynx ( n = 1) [ 49 ] and hypopharynx...…”
Section: Figurementioning
confidence: 99%
“…All FTCs with positive immunoreactivity except a single case showed an exclusive perinuclear staining which was unexpected when considering the nuclear staining of the positive control in addition to the conventional nuclear role of telomerase. However, recent studies have indeed identified predominant cytoplasmic TERT-staining patterns in other tumor types, for example in hepatocellular carcinoma where cases with cytoplasmic staining surprisingly showed a better overall prognosis [ 3 ]. TERT IHC have also been studied in papillary thyroid carcinoma where the protein is hypothesized to shift between subcellular localizations in response to oxidative stress and irradiation [ 4 ].…”
mentioning
confidence: 99%
“…Nault et al [52] found that the frequency of TERT promoter mutations increased as premalignant lesions transformed into HCC, from 6% in low-grade dysplastic nodules and 19% in high-grade dysplastic nodules to 61% in early HCC and 42% in small and progressed HCC; mutations in 10 other recurrent genes only emerged in small and progressed HCC. Similarly, Huang et al [43] demonstrated that the mutation rates also increased in a stepwise manner during advanced HCC progression and reached a maximum of 45% in patients with stage C. Calderaro et al [53] found that there were 64.6% (208/322) cases with TERT promotor mutations; HCC phenotypes were tightly associated with gene mutations, including TERT promoter mutations, and transcriptomic classification.…”
Section: Tert Promoter Point Mutationsmentioning
confidence: 93%
“…A few prominent studies on HCC demonstrated that TERT promoter mutations were found in about 30%-60% of the total cases [8,[39][40][41][42][43][44][45][46][47][48][49] . Consistent with the findings in other cancer types, the two most common mutations were C228T and C250T, and the former was more prevalent than the latter in HCC [ Table 2] [8,[39][40][41][42][43][44][45][46][47] . As shown in Table 2, there are no cases with both C228T and C250T mutations, which implies that these two hot spot *Percentage in all cancer cases; **percentage in telomerase reverse transcriptase (TERT) mutation cases mutations are mutually exclusive.…”
Section: Tert Promoter Point Mutationsmentioning
confidence: 99%
See 1 more Smart Citation